Fostering LGBTQ+ Mental Health Promotion in Non-Health Academic Programs: A Filipino Perspective. - Alibudbud, Rowalt (Health Promotion Practice, 2025)
This article emphasized the urgency of promoting LGBTQ+ mental health in the Philippines, a nation known for its friendly attitude toward LGBTQ+ individuals. Despite this, a significant portion of the population maintains negative attitudes, fostering persistent stigmatization and discrimination against gay men and lesbians. These adverse social conditions, coupled with the absence of comprehensive LGBTQ+ rights protection, exacerbate mental health disparities among LGBTQ+ individuals. Recognizing the pivotal role of educational institutions, this article explores the integration of an elective course, "LGBT+ Mental Health," within an applied behavioral science program. The curriculum was based on international reports and local studies, employing frameworks like Minority Stress and Intersectionality to scrutinize factors influencing LGBTQ+ mental health disparities. The course's blended approach encourages student engagement through discussions, group work, and assessments. Insights from the course reveal students' capacity to develop organizational programs and policies that promote mental health and inclusivity. Recommendations include expanding LGBTQ+ mental health integration beyond health-related degrees, providing support and resources, fostering a cultural shift toward acceptance within educational institutions, and tailoring the course to better respond to local LGBTQ+ needs. Moreover, the paper emphasizes the critical role of educational institutions in addressing LGBTQ+ mental health disparities, serving as a model for future progress and inclusivity. Overall, this integration of LGBTQ+ mental health promotion in a non-health academic degree program can serve as a model for institutions to advance the well-being of LGBTQ+ individuals and dismantle systemic barriers.